Genetic Characterization of mcr-1-Positive Multidrug-Resistant Salmonella enterica Serotype Typhimurium Isolated From Intestinal Infection in Children and Pork Offal in China - Zhang, Haoran; Xiang, Ying; Huang, Yong; Liang, Beibei; Xu, Xuebin; Xie, Jing; Du, Xinying; Yang, Chaojie; Liu, Hongbo; Liu, Hongbo; Wang, Hui; Yang, Mingjuan; et al. (Frontiers in Microbiology, 2022)
With the rapid emergence of plasmid-mediated colistin resistance gene mcr-1, the increased resistance of Salmonella has attracted extensive attention. This study reports on 11 multidrug-resistant Salmonella enterica serovar Typhimurium strains harboring mcr-1 in China. They all presented resistance to colistin, and additionally, one that was isolated from a child’s stool sample was also resistant to ceftriaxone and azithromycin. We screened 1454 strains of Salmonella for mcr-1 gene through PCR, and these strains are all preserved in our laboratory. Antimicrobial sensitivity analysis was carried out for the screened mcr-1 positive strains. Genetic polymorphism analysis of S. Typhimurium was performed by using the Pulsed-Field Gel Electrophoresis (PFGE). The plasmids harboring mcr-1 were identified by S1-PFGE and southern blotting. Plasmid conjugation assays were used to analyze the transferability of colistin resistance. The plasmids harboring mcr-1 were characterized by sequencing and bioinformatic analysis. Eleven S. Typhimurium strains harboring mcr-1 with colistin resistance (MICs 4μg/ml) were detected, which were isolated from children and pig offal in China. All of them were multidrug-resistant strains. PFGE results revealed that the strains isolated from different samples or locations have identical genotypes. S1-PFGE and southern blotting experiments showed that three plasmids of different sizes (33, 60, and 250 kb) all carried the mcr-1 gene. The plasmid conjugation assays revealed that Salmonella acquired mcr-1 harboring plasmids by horizontal transfer. Sequencing and plasmid type analysis revealed that these plasmids were types IncX4, IncI2, and IncHI2. Among them, IncX4 and IncI2 plasmids had extremely similar backbones and contained one resistant gene mcr-1. IncHI2 plasmid contained multiple resistant genes including blaCTX–M, oqxB, sul, aph, aadA, and blaTEM. We identified 11 mcr-1 harboring S. Typhimurium strains in China and described their characteristics. Our findings indicate that the mcr-1 gene can effectively spread among intestinal bacteria by horizontal transfer of three types of plasmids. Moreover, the IncHI2 plasmid can also mediate the transfer of other drug resistance genes. These results reveal that constant surveillance of mcr-1 harboring S Typhimurium is imperative to prevent the spread of colistin resistance.